COLLABORATIVE WORK ENVIRONMENT AND INNOVATIVE WORK BEHAVIOR: THE ROLES OF PSYCHOLOGICAL SAFETY AND KNOWLEDGE SHARING - Syahril; Siti Maria; Ariesta Heksarini (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Innovative work behavior is increasingly positioned as a source of excellence for public sector organizations amid service complexity and increasing demands for adaptation. However, the global literature does not fully explain the mechanisms by which collaborative work environments translate into employee innovation in formal, hierarchical technical bureaucracies. This study aims to analyze the influence of collaborative work environments on innovative work behavior through psychological safety and knowledge sharing among employees of the Public Works Department of the Kutai Kartanegara Regency. The study used a quantitative approach with an explanatory survey design on 174 respondents selected through proportionate stratified random sampling and analyzed using PLS-SEM. The findings indicate that collaborative work environments enhance innovative work behavior both directly and through two parallel mediation pathways: psychological safety and knowledge sharing. The theoretical contribution of this study lies in the integration of social exchange theory, psychological safety theory, and the knowledge-based view in explaining employee innovation in technical public organizations, while its practical implications emphasize the importance of cross-disciplinary work design, a culture of safe voice, and knowledge-sharing systems. The main novelty of this study lies in the parallel mediation model that simultaneously tests the psychological and epistemic pathways in the context of public sector technical bureaucracies.